Does early childhood BCG vaccination improve survival to midlife in a population with a low tuberculosis prevalence?: quasi-experimental evidence on nonspecific effects from 32 Swedish birth cohorts - Theilmann, Michaela; Geldsetzer, Pascal; Bärnighausen, Till; Sudharsanan, Nikkil (Demography, 2023)
The Bacillus Calmette-Guérin (BCG) vaccine for tuberculosis (TB) is widely used globally. Many high-income countries discontinued nationwide vaccination policies starting in the 1980s as the TB prevalence decreased. However, there is continued scientific interest in whether the general childhood immunity boost conferred by the BCG vaccination impacts adult health and mortality in low-TB contexts (known as nonspecific effects). While recent studies have found evidence of an association between BCG vaccination and survival to ages 34-45, it is unclear whether these associations are causal or driven by the unobserved characteristics of those who chose to voluntarily vaccinate. We use the abrupt discontinuation of mandatory BCG vaccination in Sweden in 1975 as a natural experiment to estimate the causal nonspecific effect of the BCG vaccine on cohort survival to midlife. Applying two complementary study designs, we find no evidence that survival to age 40 was affected by the discontinuation of childhood BCG vaccination. The results are consistent among both males and females and are robust to several sensitivity tests. Overall, despite prior correlational studies suggesting large nonspecific effects, we do not find any population-level evidence for a nonspecific effect of the BCG vaccine discontinuation on survival to age 40 in Sweden.